Innovations in Atmospheric Remote Sensing: From Satellites to Lidar and Beyond - Vaishanvi Singh (International Journal of Atmosphere, 2024)
Atmospheric remote sensing plays a vital role in monitoring and understanding the Earth's atmosphere, providing essential data for climate studies, weather forecasting, and environmental management. This review discusses various remote sensing technologies, including satellites, radiometers, lidar, radar, and GPS radio occultation, each contributing unique capabilities for atmospheric observations. Satellite remote sensing allows for global coverage and continuous monitoring of atmospheric parameters, while ground-based systems enhance localized measurements. Key applications include ozone monitoring, aerosol detection, cloud profiling, and land surface temperature assessment. Radiance measurements using infrared and microwave remote sensing techniques enable the analysis of atmospheric profiles, including total column water vapor and wind measurements. These measurements are critical for understanding climate dynamics and improving weather prediction models. The integration of airborne remote sensing with ground-based data enriches atmospheric sounding, providing a comprehensive view of atmospheric composition and structure. This review highlights advancements in remote sensing technologies, including innovations in spectral measurements and data processing techniques, which enhance the accuracy and resolution of atmospheric observations. As climate change and air quality concerns intensify, remote sensing offers invaluable insights into atmospheric phenomena, enabling better-informed decisions for environmental policy and public health initiatives. Ultimately, this review underscores the importance of ongoing research and collaboration in atmospheric remote sensing to address the pressing challenges of our time.
Keywords: Atmospheric remote sensing; GPS radio occultation; LIDAR; Radar; Satellites; aerosol remote sensing; airborne remote sensing; atmospheric profiles; atmospheric sounding; cloud remote sensing; earth observation; ground-based remote sensing; infrared remote sensing; land surface temperature; microwave remote sensing; ozone monitoring; radiometers; spectral measurements; total column water vapor; wind measurements